STRENGTHENING STUDENTS' READING LITERACY AND CRITICAL THINKING AS AN ADAPTIVE STRATEGY TO THE DEVELOPMENT OF ARTIFICIAL INTELLIGENCE IN THE DIGITAL AGE: A LITERATURE STUDY - Yudo Septian, Mohammad Arinto; Ihsani, Hanif Rizky (LPPM Universitas Bina Bangsa, 2026)
Research on the development of artificial intelligence (AI) in education has substantial implications for the learning process, particularly in strengthening students' reading literacy and critical thinking skills. A number of studies show that the unguided use of AI can trigger technological dependence, reduce the intensity of deep reading, and lower the quality of information analysis and evaluation. This condition creates an urgent need to design adaptive strategies that ensure the use of AI continues to support the development of students' cognitive capacities. This study aims to: (1) analyze the impact of AI development on reading literacy and critical thinking skills; (2) identify the urgency of strengthening these two competencies as adaptive mechanisms in the digital age; and (3) formulate an integrative AI-aware Literacy & Critical Thinking Skills model for learning at the elementary to secondary levels. The research method used a systematic literature review (SLR) with a search of national and international articles through Google Scholar, DOAJ, SINTA, and open repositories, selected based on the inclusion criteria of publication year 2018-2025, topic relevance, and full access. The results of the study show that reading literacy and critical thinking are important foundations in filtering, assessing, and verifying information generated by AI. The resulting integrative model positions AI as an augmentation tool that strengthens the processes of reading, analysis, and reflection, rather than as a substitute for cognitive activities. These findings have implications for educators and policymakers to design AI-based learning innovations that maintain academic integrity and develop students' higher-order thinking skills.